Community spread and acquisition of clinically relevant Escherichia coli harbouring blaNDM among healthy Japanese residents of Yangon, Myanmar. (24th March 2021) - Sugawara, Yo; Hagiya, Hideharu; Akeda, Yukihiro; Takeuchi, Dan; Sakamoto, Noriko; Matsumoto, Yuki; Motooka, Daisuke; Nishi, Isao; Tomono, Kazunori; Hamada, Shigeyuki
Abstract: Background: Carbapenemase-producing Enterobacterales (CPE) are spreading in hospitals, environment and retail foods in Yangon, Myanmar. Objectives: To investigate whether CPE colonize healthy individuals living in Yangon and whether clinical-related strains are spreading in the community. Methods: CPE was isolated from faecal samples obtained from healthy Japanese residents of Yangon with no history of hospitalization. Isolates were subjected to WGS using short- and long-read sequencers and compared with those previously isolated in Yangon. Results: Six Escherichia coli strains harbouring bla NDM-1 or bla NDM-5 belonging to five different STs—ST10, ST38, ST48, ST410 and ST8453—were isolated from 69 volunteers. The ST38 isolates were related to those previously isolated from retail food in Yangon. The ST410 and ST8453 isolates were highly related to previous Yangon isolates including those of clinical and food origins. Conclusions: The analysis suggested the acquisition of bla NDM -positive E. coli, which are disseminating in a clinical setting and through retail foods, by healthy residents in Yangon.